Changes in CREB activation in the prefrontal cortex and hippocampus blunt ethanol-induced behavioral sensitization in adolescent mice - Soares-Simi, Sabrina L.; Pastrello, Daniel M.; Ferreira, Zulma S.; Yonamine, Mauricio; Marcourakis, Tania; Scavone, Cristoforo; Camarini, Rosana (Frontiers in Integrative Neuroscience, 2013)
Drug dependence is a major health problem in adults and has been recognized as a significant problem in adolescents. We previously demonstrated that repeated treatment with a behaviorally sensitizing dose of ethanol in adult mice induced tolerance or no sensitization in adolescents and that repeated ethanol-treated adolescents expressed lower Fos and Egr-1 expression than adult mice in the prefrontal cortex. In the present work, we investigated the effects of acute and repeated ethanol administration on cyclic adenosine monophosphate response element-binding protein (CREB) DNA-binding activity using the electrophoretic mobility shift assay (EMSA) and the phosphorylated CREB (pCREB)/CREB ratio using immunoblotting in both the prefrontal cortex and hippocampus in adolescent and adult mice. Adult mice exhibited typical locomotor sensitization after 15 days of daily treatment with 2.0 g/kg ethanol, whereas adolescent mice did not exhibit sensitization. Overall, adolescent mice displayed lower CREB binding activity in the prefrontal cortex compared with adult mice, whereas opposite effects were observed in the hippocampus. The present results indicate that ethanol exposure induces significant and differential neuroadaptive changes in CREB DNA-binding activity in the prefrontal cortex and hippocampus in adolescent mice compared with adult mice. These differential molecular changes may contribute to the blunted ethanol-induced behavioral sensitization observed in adolescent mice.